Reading Proclus and the Book of Causes Volume 1 Western Scholarly Networks and Debates - Calma, Dragos (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2019)
Reading Proclus and the Book of Causes: Western Scholarly Networks and Debates, Volume 1 provides a fresh account, based on previously unknown documents, of the diffusion of Hellenic and Islamic thought in the Latin West (12th -16th centuries). Readership: Students/scholars interested in the history of philosophy and intellectual history, notably in the reception of Hellenic and Islamic thought in the Latin West, medieval and renaissance studies (philosophy, theology, manuscripts).